(untitled) (Eurasian Journal of History, Geography and Economics, 2023)
Special attention is paid to the scientific research carried out on improving the competitiveness of unemployed youth in the world. In this regard, scientific directions such as increasing the intellectual potential of young people in the labor market, the efficient use of the financial and credit system in increasing the competitiveness of unemployed youth, training of personnel in professions in high demand in the labor market, the development of state and non-state Employment Service in the employment of unemployed youth are gaining importance. From this, this article focuses on analyzing the competitiveness of young people in the labor market.